Estilos de vida comportamentais e motivações para adoção do estilo vegetariano entre universitários do Estado de São Paulo, Brasil - Sofia Maestre; Isabela Mazzeo; Ana Carolina Leme; Mauro Fisberg (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: Young adults have gained recognition as a period marked by changes in dietary and other lifestyle behaviors. The aim was to characterized young adults as meat and non-meat consumers and examine non-meat consumers associations between lifestyle behaviors, reasons, and motivations for adhering to vegetarian styles. METHODS: cross-sectional analysis with 692 college students from 18 to 25 years old. Participants reported socio-demographic and lifestyle characteristics. Non-meat consumers questionnaire was related to aspects of adhering a vegetarian style, and they were classified as difficulties, positive and negative aspects of adhering it. Questions related to overall health were asked. Descriptive analysis and logistic regressions were used for analyses. RESULTS: The majority of the study participants were female (79.2%) with mean age of 21.2±0.07 years. Almost 18% of the participants were non-meat consumers, from those, 78.9% reported themselves as ovo-lacto-vegetarian. Meat consumers had a higher probability for practicing less physical activity (PA) (OR 1.51; 95%CI 1.01, 2.27) and being less underweight (OR 0.22; 95%CI 0.10, 0.49) or normal weight (OR 0.48; 95%CI 0.28, 0.84) as compared to non-meat consumers. Ovo-lacto-vegetarian was more likely to reduce industrialized items (OR 3.69; 95%CI 1.18, 11.56) and less willing to do things (OR 0.10; 95%CI 0.01, 0.52) than vegan adults. CONCLUSION: Most participants were meat-consumers and had higher chances of not practicing PA and being more overweight. Vegans might be consuming more industrialized foods and were more willing to do things. Future studies should be considered to increase data generalizability in Brazil and other countries.